Methyl-2-formyl benzoate : A Review of Synthesis and Applications - Saba, Farooq; Zainab, Binti Ngaini (Bentham Science Publishers, 2018)
Methyl-2-formyl benzoate is known as a bioactive precursor in organic synthesis of compounds due to its variety of pharmacological activities namely antifungal, antihypertensive anticancer, antiulcer, antipsychotic and antiviral properties. As an active scaffold, methyl-2-formyl benzoate can be considered as a significant structure and an excellent precursor for the search of new bioactive molecules. Methyl-2-formyl benzoate is synthetically a versatile substrate, which can be used as a raw material for the preparation of medical products. Due to its significant in organic synthesis, the objective of this review is to discuss on the various synthetic routes for the preparation of methyl2-formyl benzoate (via two-step and one-step methodologies) and its importance as precursor for the preparation of compounds with pharmaceutical applications. This review is of importance in synthetic fields and pharmaceutical industry.